The Effect Of Selebgram Endorsement And Brand Trust On Purchase Decisions (Survey on Feystyle.id Shop Consumers in Tasikmalaya City) - Sriyulianti, Dina; Askolani, Askolani; Pauzy, Depy Muhamad (Journal of Management, Economic, and Accounting, 2023)
The purpose of this study was to determine the effect of celebrity endorsement and brand trust on purchasing decisions in Feystyle, Tasikmalaya City. The research method used is a quantitative method with a survey approach to 100 respondents who are Feystyle consumers. The type of data used is primary data. The data analysis technique used is multiple regression analysis. The results of this test prove that celebrity endorsements and brand trust have a significant effect both partially and simultaneously on purchasing decisions of Feystyle consumers in Tasikmalaya City.